Increased precipitation and weathering across the Paleocene‐Eocene Thermal Maximum in central China. (24th June 2016) - Chen, Zuoling; Ding, Zhongli; Yang, Shiling; Zhang, Chunxia; Wang, Xu
Abstract: Global warming during the Paleocene‐Eocene Thermal Maximum (PETM) ∼55.5 million years ago (Ma) was associated with a massive release of carbon to the ocean‐atmosphere system, as evidenced by a prominent negative carbon isotope excursion (CIE) and widespread dissolution of marine carbonates. The paleohydrologic response to the PETM warming has been studied worldwide; however, relevant records of environmental perturbation in Asia are lacking so far. Here we extend the record of this event in central China, a subtropical paleosetting, through geochemical and mineralogical analyses of lacustrine sediments. Geochemical indicators of authigenic carbonates—including molar Mg/Ca and Sr/Ca ratios—suggest an overall increased precipitation across the PETM, compatible with the disappearance of authigenic dolomite and the appearance of kaolinite in the strata. The relatively humid conditions persisted long after the carbon‐cycle perturbation had stopped, implying that the transient hyper‐greenhouse warming might have forced the regional climate system into a new climate state that was not easily reversed. Additionally, a gradual increase in chemical index of alteration (CIA) and the appearance of kaolinite are associated with the PETM, indicating an intensified silicate weathering and pedogenesis in the watershed in response to warmer and more humid climate. Our results corroborate the theory that an accelerated continental chemical weathering served as a negative feedback to sequester carbon and lower the atmospheric greenhouse‐gas levels during the PETM. Key Points: Geochemistry of authigenic carbonates and clay minerals are analyzed in central China The PETM was characterized by an overall increase in precipitation in China interior Geochemical proxies suggest an intensified continental weathering during the PETM